Market Reaction Analysis Before and After Ex-Dividend Date on Companies Listed in The Jakarta Islamic Index (JII) 2016-2020 - Adrian Dwi Nugraha (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2022)
Abstract: This study aims to examine the market reaction before and after the ex-dividend date and see whether there are differences in abnormal returns, trading volume activity, and security return variability before and after the ex-dividend date. The population in this study are companies listed in the Jakarta Islamic Index (JII) in 2016-2020 that consistently distribute dividends. The sample of this study amounted to 10 companies that consistently distribute dividends. The used method is the event study method with a window period of 10 days, 5 days before and 5 days after. The analysis technique used is the Paired Sample T-Test and the Wilcoxon-Signed Ranked Test. The results show that there are no differences in abnormal returns, trading volume activity, and security return variability before and after the ex-dividend date in the 2016-2020 Jakarta Islamic Index (JII). This shows that dividend announcements are not considered by investors in making investments.